Antimicrobial Activity of Zingiber Officinale and Allium Sativum on some Drug Resistant Bacterial Isolates - S.E. Emmanuel; E.O. Ehinmitan; R.S. Bodunde; J.C. Joseph (Journal of Applied Sciences and Environmental Management)
Ginger and garlic are very important and useful spices and are used as therapeutic agent against many pathological infections. Increasing multi-drug resistance of pathogens forces researchers to find alternative compounds for treatment of infectious diseases. In this study, the antimicrobial potency of ginger and garlic were investigated against four clinical bacterial isolates. Three types of ginger and garlic extracts (aqueous extract, methanol extract and ethanol extract) were assayed separately against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Salmonella typhi. The antibacterial activity was determined by well diffusion method. The minimum inhibitory concentration (MIC) of different bacterial species varied from 1.5625mg/ml to 5.0mg/ml with ginger extracts having the lowest and garlic extracts having the highest respectively. All tested bacterial were most susceptible to the garlic aqueous extract and showed poor susceptibility to the ginger aqueous extract. However, ginger extracts from the mean zone of inhibition have higher antimicrobial activity when compared to garlic extracts with exception to garlic aqueous extract. This study encourages the use of spices especially ginger and garlic as alternative or supplementary medicine to reduce the burden of high cost, side effects and progressively increasing drug resistance of pathogens.